BUSINESS NAVIGATION IN POLITICAL TURBULENCE: ANALYZING PRE-ELECTION ECONOMIC CONDITIONS AND ADAPTATION STRATEGIES FOR BUSINESSES - Lilis Sulastri; Iman Supratman; Avid Leonardo Sari (UIN Sunan Gunung Djati Bandung, 2023)
This literature review explores the intricate dynamics of business navigation in the face of political turbulence, with a specific focus on pre-election economic conditions and the adaptation strategies employed by businesses. The review synthesizes a range of academic sources to examine how political uncertainty, especially during election periods, influences economic environments and business operations. It delves into the various economic indicators that are typically affected by political events, such as market volatility, investment trends, and consumer confidence. The review also assesses the strategies businesses have historically adopted to mitigate risks and capitalize on opportunities during these periods of uncertainty. This includes a discussion on diversification, strategic planning, and stakeholder communication as key components of effective business adaptation. The study further explores the role of predictive analytics and scenario planning in preparing businesses for potential political outcomes and their economic repercussions. By integrating insights from various disciplines, including political science, economics, and business management, this review provides a comprehensive understanding of the challenges and strategies relevant to business decision-making in politically turbulent times. The findings highlight the importance of proactive planning and adaptability, emphasizing the need for businesses to remain agile and informed in the face of political events that can significantly impact the economic landscape.